2016
DOI: 10.1002/jnr.23835
|View full text |Cite
|
Sign up to set email alerts
|

Sodium butyrate modulates a methamphetamine‐induced conditioned place preference

Abstract: Previous studies demonstrated that histone acetylation modulated the transcription of associated gene expression and thus contributed to the persistence of addictive behaviors and neuroplasticity. Nonetheless, the roles of histone acetylation in distinct phases of methamphetamine (METH)-induced conditioned place preference (CPP) remain unclear. The current study examines the effects of the histone deacetylases (HDACs) inhibitor sodium butyrate (NaB) on the acquisition, extinction, and reinstatement of METH-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Propionate treatment reduced reward response to high‐energy foods in human (Byrne et al., 2016). Repeated sodium butyrate treatments at the EXT phase could inhibit the reinstatement of METH‐induced CPP in mice (Zhu et al., 2017). In addition, we found Prevotella was negatively correlated with SCFA metabolism at the ACQ phase.…”
Section: Discussionmentioning
confidence: 99%
“…Propionate treatment reduced reward response to high‐energy foods in human (Byrne et al., 2016). Repeated sodium butyrate treatments at the EXT phase could inhibit the reinstatement of METH‐induced CPP in mice (Zhu et al., 2017). In addition, we found Prevotella was negatively correlated with SCFA metabolism at the ACQ phase.…”
Section: Discussionmentioning
confidence: 99%
“…The doses were 4 mg/kg/d for methamphetamine, 24 mg/kg/d for nicotine, and 60 mg/kg/d for cocaine. These doses were chosen based on previous studies that indicated rewarding effects during use, resulting in withdrawal-like symptoms after the cessation of chronic use ( Johnson et al, 2008 ; Fish et al, 2010 ; Eisener-Dorman et al, 2011 ; Stoker and Markou, 2011 ; Stoker et al, 2012 ; Tracy et al, 2016 ; Zhu et al, 2017 ). Each drug was dissolved in saline, and the pH was adjusted to 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…This method of acute withdrawal was chosen to control the amount of drug each animal received and create strong dependence in a short period of time. The psychostimulant doses were chosen based on previous studies that reported rewarding effects during use and observed withdrawal-like symptoms after the cessation of chronic exposure for each drug ( Johnson et al, 2008 ; Fish et al, 2010 ; Eisener-Dorman et al, 2011 ; Stoker and Markou, 2011 ; Stoker et al, 2012 ; Tracy et al, 2016 ; Zhu et al, 2017 ). We then used single-cell whole-brain activity to identify coactivation patterns of brain regions in the network that was associated with each treatment using hierarchical clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Coadministration of VA and amphetamine upregulated CREB phosphorylation and Fos activation and attenuated locomotor activity, indicating a cascade of intracellular effects that may change the activation patterns of the neurons involved [256]. Microinjection of BA into other areas of the brain, including the amygdala and striatum, also attenuated the drug-induced locomotor activity associated with psychostimulant use [257].…”
Section: Psychostimulant Exposure During Childhood and Adolescencementioning
confidence: 94%